Analisis Pengaruh Advertising dan Public Relations Terhadap Keputusan Pembelian Produk Hijau (Studi pada Pengguna Produk Hijau The Body Shop Semarang) - Ariprayugo, Galih; Santoso, Suryono Budi (Diponegoro Journal of Management, 2016)
This study aims to analyze the influences of advertising and public relations to purchase decision in green products through brand equity of The Body Shop’s Semarang customers. Advertising and public relations are the reasons which giving special value to customer in choosing green products which are already been a lifestyle in Semarang City. Non probability sampling was used for sampling. Data were collected from 130 respondents which were selected using criteria of judgement that should have been using green products from The Body Shop Semarang. Test method is a Maximum Likelihood analysis with AMOS program version 21.0. The results showed advertising and public relations variables directly giving positive and significantly influence brand equity variable. Brand equity variable directly giving positive and significantly influence purchase decisions variable. Then, both independent variables are giving positive influence to purchase decision variable of The Body Shop Semarang green products.